Les parcs des porcelainiers Haviland - Colette Chabrely (In Situ)
The Reynou and Mont-Méry parks near Limoges originally belonged to the city’s porcelain manufacturers, the Havilands. Both parks are of considerable interest in terms of their landscaping and their botany. In both cases, there is some uncertainty as to the identity of their designers. This article offers an analysis of the graphic representations of the Reynou park, clarifying the chronology of the creation of the château and its park. For the Mont-Méry park, the aim is to offer some guidelines for further research in the source material and on the design of the park itself, perhaps allowing for the designer to be identified.